Nghiên cứu chế tạo máy chẩn đoán các loại ECU điều khiển động cơ - Đỗ Văn Dũng; Hồ Hữu Chấn; Trần Thanh Thưởng (Journal of Technical Education Science, 2006)
Today, automotive technology have developed extremely, especially automotive electric and electronic systems. Therein, ECU-Electronic Control Unit is the most complex electronic circuit and controlled by programming. It receives continuously signals from various sensors, processes and sends signals to control optimal operation of ignition and fuel injection systems. Thus, to inspect an ECU, involves high-priced dedicated devices and software. This paper introduces ECU tester with cheaper cost for using in automotive service stations and vocational institutions.